NURSING CARE IN EFFECTIVENESS OF BREATHING FOR CHRONIC OBSTRUCTION PATIENTS IN RSI NASHRUL UMMAH LAMONGAN - Dwi Anugrah, Annisa (Universitas Airlangga, 2021)
Introduction: Air pollution can cause respiratory system disorders in the form of alveoli damage, airway, and lung tissue inflammation. Inflammation of the lungs can damage the respiratory tissue and stimulate excess sputum production which causes ineffective airway clearance. This process, if it takes a long time, causes irreversible structural damage to the airway wall. This condition can progress to severe airway obstruction, called COPD. This research aims to explain nursing care for patients with Chronic Obstructive Pulmonary Disease (COPD) in the Tuberose Room at RSI Nashrul Ummah Lamongan. Methods: The research design used in this research is case study research. Participants in the study for Mr.